Progress in Nanophotonics 2 - Ohtsu, Motoichi. (Nano-Optics and Nanophotonics,, 2013)
This book focuses the recent progress in nanophotonics technology to be used to develop novel nano-optical devices, fabrication technology, and advanced systems. It begins with a review of near-field excitation dynamics in molecules. Further topics include: wavelength up-converting a phonon-assisted excitation process with degenerate beams and non-degenerate beams in dye grains, a fabrication method of semiconductor quantum dots including self-assembly of InAs quantum dots based on the Stranski-Krastanov growth mode, single-nanotube spectroscopy and time-resolved spectroscopy for studying novel excitonic properties of single-walled carbon nanotubes. The striking features of ecxitons in the carbon nanotube, multiple-exciton states, and microfluidic and extended-nano fluidic techniques. These topics are reviewed by nine leading scientists. This overview is a variable resource for engineers and scientists working in the field of nanophotonics.